2020
DOI: 10.3174/ajnr.a6674
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal Carotid Artery Thrombus in COVID-19: Another Danger of Cytokine Storm?

Abstract: Coronavirus disease 2019 (COVID-19) is associated with a severe inflammatory response. Inflammation affects atherosclerotic plaque vulnerability and promotes a thrombogenic environment. We report a series of 6 patients with COVID-19 with acute ischemic stroke due to intraluminal carotid artery thrombus presenting during an 8-day period. Six patients were included (5 men) with a mean age of 65.8 years (range, 55-78 years). COVID-19 was diagnosed by detection of Severe Acute Respiratory Syndrome coronavirus 2 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 19 publications
6
56
1
3
Order By: Relevance
“…Like our patient, the carotid thrombus resolved with anticoagulation and no invasive intervention. The largest series of carotid thrombotic complications from COVID-19 identified six patients with carotid thrombosis and artery-to-artery embolism leading to stroke 25 . However, typical vascular risk factors and plaque rupture from prior atherosclerosis from the pro-inflammatory state was thought to be the cause of carotid thrombosis in this series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like our patient, the carotid thrombus resolved with anticoagulation and no invasive intervention. The largest series of carotid thrombotic complications from COVID-19 identified six patients with carotid thrombosis and artery-to-artery embolism leading to stroke 25 . However, typical vascular risk factors and plaque rupture from prior atherosclerosis from the pro-inflammatory state was thought to be the cause of carotid thrombosis in this series.…”
Section: Discussionmentioning
confidence: 99%
“…• Case presentation A 50-year-old male, former smoker, with history of T3N0M0 laryngeal squamous cell carcinoma status post total laryngectomy, partial pharyngectomy, laryngostomy, bilateral neck dissection, and anterolateral thigh free flap with 1 month of post-operative neck radiation three years prior to this event presented with acute stroke. He has a history of hypothyroidism, provoked identified six patients with carotid thrombosis and artery-to-artery embolism leading to stroke 25 .…”
Section: • Introductionmentioning
confidence: 99%
“…We found no evidence to support previous suggestions that SARS-CoV-2 infection may be associated with a younger age 7,10 or male sex 7 in stroke patients. In the case-control study from New York 7 mechanisms, promoting generation of thrombus in the heart 20 or large vessels 10,21 or via small vessel occlusion 22 . Which of these mechanisms manifests in a given patient may be determined by thatindividual's conventional vascular risk factors such as atrial fibrillation, large vessel atheroma, hypertensionor type 2 diabetes mellitus.…”
Section: Outcome From Strokementioning
confidence: 99%
“…There are many reports of early COVID-19 presenting with thrombotic events, which has led to the consensus to start anticoagulation therapy early in the COVID-19 disease course before any thrombotic event. There are reports in the literature specifically addressing macrothrombosis in the internal carotid artery in patients with mild respiratory symptoms of COVID-19 14 , 15 and stroke as a presenting symptom of the disease. 12 A multicentre series of 26 patients with COVID-19 and either ischaemic or haemorrhagic events reported that 27% were younger than 50 years.…”
mentioning
confidence: 99%